Makna Otonomi Ekonomi Perempuan dalam Lagu Miss Independent: Analisis Semiotika Roland Barthes - Fellycia Muaya; Diah Ayu Candraningrum (Fakultas Ilmu Komunikasi Universitas Tarumanagara, 2026)
This study examines the representation of perceptions of women’s economic autonomy in Ne-Yo’s